2018
DOI: 10.1002/anie.201802231
|View full text |Cite
|
Sign up to set email alerts
|

A Durable Nickel Single‐Atom Catalyst for Hydrogenation Reactions and Cellulose Valorization under Harsh Conditions

Abstract: Hydrothermally stable, acid-resistant nickel catalysts are highly desired in hydrogenation reactions, but such a catalyst remains absent owing to the inherent vulnerability of nickel under acidic conditions. An ultra-durable Ni-N-C single-atom catalyst (SAC) has now been developed that possesses a remarkable Ni content (7.5 wt %) required for practical usage. This SAC shows not only high activities for hydrogenation of various unsaturated substrates but also unprecedented durability for the one-pot conversion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
176
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(180 citation statements)
references
References 49 publications
4
176
0
Order By: Relevance
“…DFT calculations and XANES analyses have shown that on N‐doped carbon, the active‐centre structure is Ni‐N 4 , and that an unusual heterolytic dihydrogen activation mode on a frustrated Lewis pair occurs . Indeed, when H 2 approaches the Ni‐N 4 centre, it is activated via an interaction with Ni and the adjacent pyridinic N atoms.…”
Section: Catalysis With Single Atom Catalysts On Carbon‐based Materialsmentioning
confidence: 99%
“…DFT calculations and XANES analyses have shown that on N‐doped carbon, the active‐centre structure is Ni‐N 4 , and that an unusual heterolytic dihydrogen activation mode on a frustrated Lewis pair occurs . Indeed, when H 2 approaches the Ni‐N 4 centre, it is activated via an interaction with Ni and the adjacent pyridinic N atoms.…”
Section: Catalysis With Single Atom Catalysts On Carbon‐based Materialsmentioning
confidence: 99%
“…Single‐atom Ni−N‐C and CoN x C catalysts demonstrated high activity in one‐pot conversion of cellulose and selective dehydrogenation of formic acid, respectively. Liu et al . proposed an active site (NiN 4 )⋅⋅⋅N in which the nickel atom is coordinated by four pyridinic nitrogen atoms.…”
Section: The Particle Size Of Palladium In the Catalysts And The Co/pmentioning
confidence: 99%
“…[7] The metal ions were shownt ob er esponsible for higha ctivity and selectivity in formic acid decomposition. Quantum chemical calculations allowed us to propose the active site represented by the metal ion coordinated by two pyridinic nitrogen atoms at the edge of graphene sheets.Single-atom NiÀN-C and CoN x Cc atalysts demonstratedh igh activity in one-potconversion of cellulose [8] and selective dehydrogenation of formic acid, [9] respectively.L iu et al [8] proposed an active site (NiN 4 )···N in which the nickel atom is coordinated by four pyridinic nitrogen atoms. Li and co-workers described the synthesis of single-atom Wand Co catalysts with metal coordination by one or four pyridinic nitrogen atoms of N-C, showingh igha ctivity in electrochemical, hydrogenation, and dehydrogenation reactions.…”
mentioning
confidence: 99%
“…[18][19][20][21] For some compounds, their unsaturated C=Obond makes them exhibit special features. [27,29,30] Denga nd Liu investigated the catalytic performance of Ni-SnO x of with Sn/Ni ratios in ar ange of 0-2.0 and proposed that the SnO x species were responsible for the selective cleavage of the CÀCb onds in glucose and fructose. Keto-alcohols, whichp ossessh ydroxy and carbonyl groups,a re among the high-value-added organic compounds and could potentially be used for many organic syntheses.…”
mentioning
confidence: 99%
“…[25,27,28] It also can be obtained by direct conversion cellulose over Ni-based catalysts such as Ni-SnO x /Al 2 O 3 or single-atom Ni catalysts. [27,29,30] Denga nd Liu investigated the catalytic performance of Ni-SnO x of with Sn/Ni ratios in ar ange of 0-2.0 and proposed that the SnO x species were responsible for the selective cleavage of the CÀCb onds in glucose and fructose. [23] HB is mainly used to synthesize ethambutol, acommon anti-tuberculosis drug.…”
mentioning
confidence: 99%